Effects of Co‐administration of Sulfonylureas and Antimicrobial Drugs on Hypoglycemia in Patients with Type 2 Diabetes Using a Case‐Crossover Design. Issue 9 (13th August 2020) - Lee, Sera; Ock, Miyoung; Kim, Hun‐Sung; Kim, Hyunah
Abstract : Objectives: The purpose of this study was to investigate the effect of sulfonylureas (SUs) and antimicrobial co‐administration on hypoglycemia in patients with type 2 diabetes mellitus (T2DM). Methods: We conducted a case‐crossover study using the Korean Health Insurance Review and Assessment Service‐National Inpatient Sample database, using data from 2014 to 2016. Hospitalized adult patients with T2DM who were diagnosed with hypoglycemia and prescribed SUs for at least 120 days were included. Different risk ratings of severity of drug–drug interactions were considered, including "level X, D, or C" in Lexi‐Interact online and "contraindicated, major, or moderate" in Micromedex. Exposure to antimicrobials in the 30‐day period before the first hypoglycemia diagnosis was assessed. Two control periods (61–90 and 91–120 days) were matched before the diagnosis date. Conditional logistic regression analysis was conducted to compare the odds of antimicrobial exposure. Results: A total of 9339 patients were included. The mean age of the patients was 71.3 ± 10.6 years, and 4818 (51.6%) were women. An increased risk of hypoglycemia was associated with co‐administration of SUs and certain antimicrobials (adjusted odds ratio [aOR] 2.56, 95% confidence interval [CI] 2.34–2.80). The antimicrobial agents that were associated with an increased risk of hypoglycemia, when co‐administered with SUs, were sulfonamides (aOR 2.99, 95% CI 1.99–4.52), fluoroquinolones (aOR 2.62, 95% CI 2.38–2.89), macrolides (aOR 2.48, 95% CI 1.88–3.27), and tetracyclines (aOR 1.56, 95% CI 1.05–2.33). Conclusions: Co‐administration with SUs and certain antimicrobials increased the risk of hypoglycemia. Thus, clinically relevant interactions in patients concurrently using SUs and antimicrobials should be monitored, especially within 30 days after co‐administration.